2023
DOI: 10.3390/nu15112478
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Metabolic Syndrome and Religious Fasting in Postmenopausal Women

Abstract: Religious fasting that involves abstinence from specific food(s) is part of many religions worldwide and has been gaining attention by the research community during the last years. The study aimed to investigate whether the periodic Christian Orthodox fasting mitigates the changes in body composition, dietary intake, and metabolic syndrome (MetS) in postmenopausal women. One hundred and thirty-four postmenopausal women aged 57.3 ± 6.7 years participated in this study. The Christian Orthodox fasting was followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…However, a recent cross-sectional study on 175 individuals aged >50 years showed no differences in anthropometric parameters among fasters and non-fasters, except for the hip circumference, with fasters having higher mean values than non-fasters [ 18 ]. Another study conducted on 134 postmenopausal women aged 57.3 ± 6.7 years demonstrated that postmenopausal female fasters had a significantly higher mean fat free mass, hip circumference and diastolic blood pressure, while no other differences were found with regards to their anthropometric data [ 55 ]. However, these discrepancies may be attributed to the fact that the study population was exclusively restricted to postmenopausal women [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent cross-sectional study on 175 individuals aged >50 years showed no differences in anthropometric parameters among fasters and non-fasters, except for the hip circumference, with fasters having higher mean values than non-fasters [ 18 ]. Another study conducted on 134 postmenopausal women aged 57.3 ± 6.7 years demonstrated that postmenopausal female fasters had a significantly higher mean fat free mass, hip circumference and diastolic blood pressure, while no other differences were found with regards to their anthropometric data [ 55 ]. However, these discrepancies may be attributed to the fact that the study population was exclusively restricted to postmenopausal women [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted on 134 postmenopausal women aged 57.3 ± 6.7 years demonstrated that postmenopausal female fasters had a significantly higher mean fat free mass, hip circumference and diastolic blood pressure, while no other differences were found with regards to their anthropometric data [ 55 ]. However, these discrepancies may be attributed to the fact that the study population was exclusively restricted to postmenopausal women [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data on clinical history, education, marital status, physical activity levels, sedentary time spending watching television and/or using the computer, time sleeping, smoking status, and alcohol consumption, among others, were collected via open-ended and closed questions. More details regarding data collection and measurements were already published [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…As MetS remains a public health issue, the relationship of the Mediterranean diet, and more specifically, the COC recommendations along with its risk factors, needs further investigation. Up to date, a few studies focusing on the effects of COC on MetS risk factors have been carried out in Greece [ 28 , 29 , 30 , 31 , 32 ], Africa [ 33 , 34 , 35 ], and the USA [ 36 , 37 ]. The initial aim of this study was to identify the dietary patterns followed by a COC fasting population and a non-fasting population in Greece, and secondly, to investigate any relationships between the dietary patterns and MetS risk factors and prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who fasted regularly since their childhood, or for at least the last twelve consecutive years, formed the COC fasting group (n = 200, 131 women), whereas those who did not fast and/or follow any other restrictive dietary pattern, such as avoidance of wheat and/or lactose, formed the non-fasting group (n = 200, 126 women). More details about the inclusion/exclusion criteria and the study population have been described previously [25,26]. The protocol was approved by the Bioethics Committee of the Alexander Technological Educational Institute of Thessaloniki (∆Φ 31-5/5679, date 17 December 2013).…”
Section: Study Populationmentioning
confidence: 99%